Australians' shifting concerns about mis- and disinformation. Issue 3 (3rd July 2022) - McGuinness, Kieran; Fisher, Caroline; Lee, Jee Young
ABSTRACT: Prior to COVID-19, trust in news was low, and Australian audiences were most concerned about mis- and disinformation from Australian political actors, followed closely by news outlets. Twelve months on trust in news had risen, and concern about misinformation from journalists and politicians had fallen dramatically. This shift followed increased news consumption and high satisfaction with the way governments managed the pandemic – prior to the immunisation roll out. This paper draws on data from five national Australian surveys conducted by the News & Media Research Centre at the University of Canberra. The data show that changes in news consumption, trust in news, and concern about mis- and disinformation coincided with a rally-round-the-flag effect in politician approval, but this varied depending on the political orientation and age of audiences. The findings suggest that a range of media-related factors may be possible contributors to political rallying effects and warrant further investigation.